Blockchain to Advance Agrarian Business - Nadiia P. Reznik, Yuriy P. Gumeniuk, Olena O. Gumeniuk, Oksana Y. Huhul, Ludmyla M. Seheda (International Journal of Advanced Science and Technology, 2020)
New technologies so as Block-chain, virtual and augmented reality technologies, Computer Vision, Image Recognition and so on have penetrated all fields of human activity, and recently have been applied even in agriculture. Development of technologies also influences an advance of food production and motivates the appearance of new human professions and new supply and demand for services. In order to understand the future of innovative technologies in the field of agricultural enterprises, it is necessary to forecast what technologies have more perspectives in the future and what connected with its challenges will arise in the near tomorrow. Besides, it is needed to understand the condition of the current technology market, which actively develops or only just begins to be applied into the agricultural sector, to choose the most perspective technologies that can use to improve agricultural business.